2019
DOI: 10.1073/pnas.1910097116
|View full text |Cite
|
Sign up to set email alerts
|

Sterile activation of invariant natural killer T cells by ER-stressed antigen-presenting cells

Abstract: Invariant NKT (iNKT) cells have the unique ability to shape immunity during antitumor immune responses and other forms of sterile and nonsterile inflammation. Recent studies have highlighted a variety of classes of endogenous and pathogen-derived lipid antigens that can trigger iNKT cell activation under sterile and nonsterile conditions. However, the context and mechanisms that drive the presentation of self-lipid antigens in sterile inflammation remain unclear. Here we report that endoplasmic reticulum (ER)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 77 publications
1
29
0
Order By: Relevance
“…In contrast to the pro-inflammatory effect of PA in macrophages, a recent study found that PA enhanced the degradation of RIDD on T-bet and gata-3 mRNA by inducing ER stress in iNKT cells, thereby suppressing the production of IL-4 and IFN-γ and attenuating arthritis ( Ko et al, 2017 ). In addition, ER stress induced IRE1α and PERK-dependent branches can increase lipid antigens bound to CD1d molecules, thereby enhancing iNKT cell activation ( Bedard et al, 2019 ; Govindarajan et al, 2020 ). This indicates that ER-stressed APCs can affect iNKT cell activation via CD1d.…”
Section: Endoplasmic Reticulum Quality Control and Immune Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the pro-inflammatory effect of PA in macrophages, a recent study found that PA enhanced the degradation of RIDD on T-bet and gata-3 mRNA by inducing ER stress in iNKT cells, thereby suppressing the production of IL-4 and IFN-γ and attenuating arthritis ( Ko et al, 2017 ). In addition, ER stress induced IRE1α and PERK-dependent branches can increase lipid antigens bound to CD1d molecules, thereby enhancing iNKT cell activation ( Bedard et al, 2019 ; Govindarajan et al, 2020 ). This indicates that ER-stressed APCs can affect iNKT cell activation via CD1d.…”
Section: Endoplasmic Reticulum Quality Control and Immune Cellsmentioning
confidence: 99%
“…Associated with T cell exhaustion in the TME (Ma et al, 2019) Regulate the anti-tumor activity of CD8 + T cell (Cao et al, 2019) Unknown Unknown NK and NKT Unknown Required for NK cell expansion (Dong et al, 2019). Regulate NKT1 and NKT17 cell effector functions and iNKT cell activation (Govindarajan et al, 2018(Govindarajan et al, , 2020 Regulate iNKT cell activation (Bedard et al, 2019) Unknown Unknown…”
Section: Macrophagementioning
confidence: 99%
“…For a detailed technical description, we refer the reader to ( 62 64 ). In immunology, these traditional techniques and their advancements have, for instance, been used to investigate the diffusion properties of key signaling molecules such as BCR, CD1d, TCR, CD45, or Lck in live cells ( 65 74 ).…”
Section: From Fluorescence Imaging To Quantification Of Dynamicsmentioning
confidence: 99%
“…It is generally assumed that the iNKT cell TCR repertoire is solely generated by positive selection resulting from the interactions of the precursors with CD1d-agonistic ligand complex and SLAM (signaling lymphocyte activation molecule) receptors on DP thymocytes (5,(30)(31)(32)(33)(34)(35)(36)(37). Nonetheless, indirect evidence supports a role for negative selection in sculpting a functional iNKT cell TCR repertoire (38)(39)(40)(41)(42), potentially weeding out highaffinity self-reactive iNKT cells.…”
Section: Significancementioning
confidence: 99%
“…iNKT cell functions are controlled by self and nonself lipid agonists presented by MHC-like CD1d molecules (1)(2)(3)(4). This recognition of self-agonists by iNKT cells, especially in the context of sterile inflammation (5), warrants an in-depth investigation of tolerance induction mechanisms in iNKT cells.…”
mentioning
confidence: 99%